2017
DOI: 10.18203/2320-1770.ijrcog20175263
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of asymptomatic bacteriuria among antenatal women attending a health care center: one year study

Abstract: Background: Asymptomatic bacteriuria is defined as presence of persistent and actively multiplying bacteria in urine in significant numbers, ≥10 5 /ml but without clinical symptoms. Detection of ASB is important during pregnancy as it leads to 25% of symptomatic urinary tract infection in pregnant mothers, pyelonephritis, hypertension in pregnancy, postpartum UTI, anemia, preterm labour, low birth weight and perinatal death of the foetus. The objective of the present study is to identify the prevalence of ASB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Gram-negative isolates were highly sensitive to nitrofurantoin, meropenem, imipenem, piperacillin-tazobactam, and fosfomycin in our study, which is similar to other studies. [ 10 21 22 23 ] In E. coli , norfloxacin is 50% resistant similar to other studies. [ 24 ] Ampicillin is nearly 50% sensitive in E. coli similar to another study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Gram-negative isolates were highly sensitive to nitrofurantoin, meropenem, imipenem, piperacillin-tazobactam, and fosfomycin in our study, which is similar to other studies. [ 10 21 22 23 ] In E. coli , norfloxacin is 50% resistant similar to other studies. [ 24 ] Ampicillin is nearly 50% sensitive in E. coli similar to another study.…”
Section: Discussionsupporting
confidence: 82%
“…[ 23 ] Most E. coli and Klebsiella isolates in our study were found nearly 80%–85% sensitive to nitrofurantoin which is concordance with other studies. [ 21 23 ] However, another study showed 100% sensitivity of nitrofurantoin to E. coli and Klebsiella [ 2 ] [ Table 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in a comparable South Indian population by Cooly et al . [ 1 ] and Udawat et al . [ 11 ] have also shown similar prevalence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women are more susceptible to ASB because of the various morphological, hormonal, and physiological changes the body undergoes during gestation. The short-sized urethra and the proximity of the urinary tract to the anal canal in females poses an increased risk of contamination by fecal flora[ 1 ] which when combined with the apparent reduction in immunity during pregnancy along with the glycosuria that is seen in 70% of the women during gestation promotes a suitable environment for the proliferation of bacteria in the urinary tract. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%